2009
DOI: 10.1007/s10661-009-0952-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of personal–indoor–ambient fine particulate matters among school communities in mixed urban–industrial environment in India

Abstract: The present study is focused on the relationship of school community personal exposure of respirable particulate matter (RPM) with its indoor and ambient outdoor component. A representative longitudinal study design has been adopted. School community is divided into two categories: (1) subjects of science discipline and (2) subjects of nonscience discipline. On the basis of local meteorological parameters and school building constructions, three schools have been identified for the study. Selected subjects hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
2
4
1
Order By: Relevance
“…Except for the offices in Belgium, the concentrations in this study were obviously lower compared to others [ 22 – 25 , 28 31 ]. Several factors influenced the concentrations of PM 2.5 , PM 10 , and TSP in indoor air.…”
Section: Resultscontrasting
confidence: 83%
“…Except for the offices in Belgium, the concentrations in this study were obviously lower compared to others [ 22 – 25 , 28 31 ]. Several factors influenced the concentrations of PM 2.5 , PM 10 , and TSP in indoor air.…”
Section: Resultscontrasting
confidence: 83%
“…But the indoor PM concentrations were lower than those reported previously for Delhi, India (Goyal and Khare, 2009). However, they were comparable to those of studies conducted in Chhattisgarh, India (Gadkari, 2010) and Hong Kong (Lee and Chang, 2000). The differences in PM concentrations were correlated with the location of school, seasons, and time period of measurement.…”
Section: Resultssupporting
confidence: 79%
“…Janssen et al (2001) also observed that PM 2.5 and soot concentrations in both indoor and outdoor air at schools in the Netherlands were significantly increased with increasing density of truck traffic. Gadkari (2010) studied the indoor fine PM among school communities in mixed urbanindustrial environment in India and reported that school located near the steel plant have shown 5-6 times higher values of respirable PM compared with National Ambient Air Quality Standards (NAAQS). Several investigators have compared the PM concentration in different indoor environments such as classrooms, library, administrative office, laboratory, etc., in same school building (Sawant et al, 2004;Diapouli et al, 2008;Gaidajis and Angelakoglou, 2009) and concluded that the resuspension of particles due to occupants' activities plays an important role in indoor coarse particle concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the existence of the NEAP might depend on the context of indoor environment or outdoor environment. As an individual may spend most of their time indoors, and some studies have found that indoor and ambient outdoor pollutants have strong positive relationships [37], others find that total personal fine particle exposures were dominated by exposure to non-ambient indoor particles [38]. Therefore, it is useful to separate exposure to ambient outdoor components from non-ambient indoor ones.…”
Section: Introductionmentioning
confidence: 99%